Money Illusion and Economic Education, an Experimental Approach - Chytilová, Helena (2012)
Money illusion has played a minor role in explaining business cycles since the revolution of rational expectations. It recaptured its significance again through the contributions of Fehr and Tyran (2001). With the application of experimental methods, evidence exists of the significant effect of money illusion intensifying coordination failure in their artificial economy. As a result, monetary shocks might cause significant long-lasting deviations of the economy from its equilibrium, thereby strengthening the predictions of the New Keynesian model. This thesis follows the latest research, and with the aid of similar experimental methods tries to verify whether the acquisition of economic education has weakening or even suppressive effects on money illusion itself. If the aforementioned hypothesis is proven, it can lead to a situation where qualified economic professionals might contribute to a reduction of money illusion in the economy, either directly by setting prices, or indirectly as consultants. At the aggregate level, it implies limited loss of effectiveness caused by changes in monetary policy owing to a faster drift of the economy to a new equilibrium. Our findings suggest that even well-educated individuals do not have the ability to pierce the veil of money and do not form expectations properly after a fully anticipated monetary shock. As a result, New Keynesian predictions about the short run non-neutrality of money might be reinforced. Further analysis demonstrates that even a well-educated individual who is not subject to money illusion is seriously constrained in his coordination effort due to unfavorable conditions prevailing at the aggregate level. Our conclusions are also supported by the individual and aggregate level analysis which evaluated the willingness of individuals to coordinate.